Comparative proteomic analysis of astrocytoma tissues from patients with and without seizures - Thanakorn Khaosuwan; Kittinun Leetanaporn; Pongsakorn Choochuen; Raphatphorn Navakanitworakul; Anukoon Kaewborisutsakul; Thara Tunthanatip; Surasak Sangkhathat; Wararat Chiangjong; Kanitpong Phabphal (Scientific Reports)
Abstract Astrocytoma is a common type of glioma and a frequent cause of brain tumour-related epilepsy. Although the link between glioma and epilepsy is well established, the precise mechanisms underlying epileptogenesis in astrocytoma remain poorly understood. In this study, we performed proteomic analysis of astrocytoma tissue from patients with and without seizures using mass spectrometry-based techniques. We detected 131 differentially expressed proteins (42 upregulated and 89 downregulated). Proteins upregulated in patients with seizures were mostly related to an increase in energy metabolism. Moreover, glial fibrillary acidic protein, which is involved in maintaining normal axonal structures, was abnormally highly expressed in patients with seizures. Proteins downregulated in patients with seizures included those involved in trans-synaptic signalling and gamma-aminobutyric acid synaptic transmission. Interestingly, comparison of protein expression profiles from our cohort with those from a previous study of patients with epilepsy due to other causes showed that the collapsin response mediator protein family of axonal growth regulators was highly expressed only in patients with seizures due to astrocytomas. Further studies of the proteins identified here are required to determine their potential as biomarkers and therapeutic targets.